Scuttle flies (Diptera: Phoridae) caught at dead mice in S. W. Finland - Disney, R. Henry L. (Zootaxa, 2012)
Scuttle flies trapped at baits of dead mice are reported from a region of S. W. Finland subjected to pollution from the smelt-ing of copper and nickel. Most belonged to the huge genus Megaselia, but 96% were females, the majority of which cannot be named until linked to their males. These are given code numbers and distinguished by means of a key.